Analysis of the association of chronic spontaneous urticaria with interlekin-4, -10, transforming growth factor-β1, interferon-γ, interleukin-17A and -23 by autologous serum skin test - Degirmenci, Papatya Bayrak; Kırmaz, Cengiz; Vatansever, Seda; Onur, Ece; Nal, Emine; Erdin, Soner; Ozyurt, Beyhan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Aim : To contribute to the understanding of the pathogenesis of chronic spontaneous urticaria (CSU) by identifying its relationship with autoimmunity and cytokines using the autologous serum skin test (ASST) and peripheral blood mononuclear cell culture (PBMC) method. Material and methods: Interleukins (IL)-4, IL-10, transforming growth factor (TGF-β1), interferon (IFN)-γ, IL-17A, and IL-23 levels in cell supernatants obtained by the PBMC method were measured using ELISA. Disease activity was assessed by determining the urticaria activity score (UAS). Results : A total of 40 patients diagnosed with CSU participated in this study. Twenty patients had positive ASST results, and 20 had negative results. The control group included 20 healthy volunteers. We found that the IL-23 (p = 0.01), IL-10 (p = 0.04) and IL-4 (p = 0.04) levels of the patient groups were significantly lower compared with those of the control group. The IL-23 (p = 0.009), IL-10 (p = 0.009), IL-4 (p = 0.001), and IL-17 (p = 0.05) levels of the ASST(–) patient group were significantly lower compared with those of the control group. In addition, the IL-4 (p = 0.03) and IFN-γ (p = 0.05) levels of the ASST(+) patient group were significantly lower compared with those of the control group, and the ASST(+) patients had a significantly higher UAS than the ASST(–) patients (p = 0.021). Conclusions : These results, when considered together with current reports in the literature, indicate that immune dysregulation occurs in the pathogenesis of CSU, causing cytokine imbalance.